The suplementation of fibre degrading enzymes and phytase in poultry diet on the performance of broiler chickens - Sisca Tirajoh; W.G. Piliang; P.P. Ketaren (Jurnal Ilmu Ternak dan Veteriner, 2010)
Most poultry feed in Indonesia are imported while some of local feed such as rice bran is available throughout the year. Rice bran contains fiber and phytic acid so it needs to be supplemented with degrading enzymes and phytase to be used as poultry feed. This experiment was aimed to evaluate the effect of various levels of degrading enzymes and phytase on performances of broiler chickens fed diet containing rice bran. Based on Completely randomized design, a number of 280 of day old chicks (unsexed) were allotted to receive 7 experimental diets: (i). P1 = basal diet (control); (ii). P2 = P1 + natugrain: xylanase 1650 EXU + β-glucanase 1200 BGU/kg; (iii). P3 = P1 + phytase 500 FTU/kg; (iv). P4 = P1 + phytase 1000 FTU/kg; (v). P5 = P1 + fibre degrading enzymes (PU42 + BS4) 7,5 unit /kg; (vi). P6 =  P1 + fibre degrading enzymes (PU4-2 + BS4) 7.5 unit /kg + phytase 500 FTU/kg; (vii). P7 = P1 + fibre degrading enzymes (PU4-2 + BS4) 7.5 unit/kg  + phytase 1000 FTU/kg. The chickens were fed and given water ad lib for 6 weeks and then some were slaughtered for carcass evaluation. Results showed that supplementation of 1000 FTU/kg phytase to the diet improved feed efficiency and percentage of breast weight of chickens significantly (P<0.05). Supplementation of other levels of phytase, fiber degrading enzymes and its combination levels into the diets did not affect feed consumption and live weight gain of the chickens. Key words: Broiler Chickens, Fiber Degrading Enzymes, Phytase